An intracerebral mass: tuberculosis or sarcoidosis?. (2nd May 2013) - Tuna, Tibel; Ozkaya, Sevket; Dirican, Adem; Erkan, Levent
Abstract : Sarcoidosis is an idiopathic, chronic granulomatous disease and it can affect almost any organ. In autopsy series, it has been reported that the central nervous system involvement has occurred in 5–16% of the patients with sarcoidosis, while the neurological symptoms have occurred only in 3–9% of them. A 40-year-old female patient was admitted to the hospital with complaints of aphasia, balance disorder and drowsiness. An intracerebral mass was detected on cranial CT scans and neurosarcoidosis was diagnosed with clinical, radiological and histopathological findings.